Efeito da degradação de concreto a diferentes temperaturas nas propriedades mecânicas e tenacidade à fratura - Nunes, Débora de Almeida (2022)
The probability of a fire occurring in buildings is small; however, if it does occur, its impact on the structure can be high. Therefore, the study of post-fire concrete structures is an area that still requires many advances in research. Based on this, it is crucial to know the performance of concrete after exposure to high temperatures, including tracking changes in the characteristics and properties of the material. This work sought to investigate the influence of high temperatures on fracture toughness (KIC), compressive strength and ultrasonic pulse velocity (UPV) in concrete; as well as to investigate possible changes in the microstructure of the material. For this purpose, concrete specimens with two strength classes, 25 MPa and 40 MPa, commonly used in concrete structures, were dosed and molded. The temperatures chosen for simulating fire conditions were 400 °C and 800 °C, because at these levels more pronounced degradation of this material and decrease of its mechanical properties are expected. The specimens were molded into two geometries: cylindrical, for compressive strength testing; and prismatic for the ultrasound test and subsequent bending test in three points to obtain KIC. Assays were performed for two test ages: 100 and 720 days. Thus, there was a significant reduction in the values of compressive strength and UPV with increasing temperature, and only a downward trend for KIC values. This is possibly due to degradation of concrete constituents.